2012
DOI: 10.1007/s00418-012-1018-0
|View full text |Cite
|
Sign up to set email alerts
|

An anti-inflammatory role for leukemia inhibitory factor receptor signaling in regenerating skeletal muscle

Abstract: Skeletal muscle regeneration in pathology and following injury requires the coordinated actions of inflammatory cells and myogenic cells to remove damaged tissue and rebuild syncytial muscle cells, respectively. Following contusion injury to muscle, the cytokine leukemia inhibitor factor (LIF) is up-regulated and knockout of Lif negatively impacts on morphometric parameters of muscle regeneration. Although it was speculated that LIF regulates muscle regeneration through direct effects on myogenic cells, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 68 publications
(82 reference statements)
0
35
0
Order By: Relevance
“…The increased muscle strength observed in this investigation is highly likely to be related to the significant increase in macrophage expression of pro-regenerative factors insulin-like growth factor 1 (Barton et al, 2002), leukemia inhibitory factor (Barton et al, 2002;Hunt et al, 2013), and urokinase plasminogen activator (Suelves et al, 2007;Bryer et al, 2008). At the same time, no significant difference was observed in the expression of profibrotic factors such as fibronectin (Vidal et al, 2008;To and Midwood, 2011), C-C chemokine ligand 17 (Belperio et al, 2004;Yogo et al, 2009), and TGF-β (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The increased muscle strength observed in this investigation is highly likely to be related to the significant increase in macrophage expression of pro-regenerative factors insulin-like growth factor 1 (Barton et al, 2002), leukemia inhibitory factor (Barton et al, 2002;Hunt et al, 2013), and urokinase plasminogen activator (Suelves et al, 2007;Bryer et al, 2008). At the same time, no significant difference was observed in the expression of profibrotic factors such as fibronectin (Vidal et al, 2008;To and Midwood, 2011), C-C chemokine ligand 17 (Belperio et al, 2004;Yogo et al, 2009), and TGF-β (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…8 A). On the contrary, OPN −/− mdx macrophages showed significantly increased expression of pro-regenerative factors, such as insulin-like growth factor 1 (Barton et al, 2002), leukemia inhibitory factor (Hunt et al, 2013), and urokinase plasminogen activator (Suelves et al, 2007; Fig. 8 B).…”
Section: Opn Ablation Promotes the Expression Of Pro-regenerative Facmentioning
confidence: 99%
“…The sources of cells which can produce LIFR cytokines that are capable of exerting effects on muscle appear to include most of these possibilities; one such example is that macrophages can produce LIF and this acts as a chemotactic factor for myogenic precursor cells (Robertson et al 1993 ). We observed LIF immunoreactivity in injured muscle deriving from mononucleated cells, which could include infl ammatory cells such as macrophages or neutrophils (Hunt et al 2013 ). Nerve injury increases LIF expression and therefore the neurons or glial Schwann cells that comprise the nerve could be a source of LIF that can regulate muscle homeostasis (Ito et al 1998 ).…”
Section: Varied Sources Of Lifr Cytokines Regulating Muscle and Peripmentioning
confidence: 88%
“…Fulfi lling this defi nition, LIF and other LIFR cytokines are indeed myokines. Whilst monitoring the administration of a LIF mutant, we detected a signifi cant increase in circulating endogenous LIF in the control group shortly after muscle injury (1 day) (Hunt et al 2013 ). This suggested that muscle damage may be one such stimulus, in addition to the aforementioned muscle stimulation or exercise, which induces LIF and myokine expression capable of acting as an endocrine.…”
Section: Varied Sources Of Lifr Cytokines Regulating Muscle and Peripmentioning
confidence: 95%
“…The expression profile of Has2 associated best with macrophage accumulation or myoblast differentiation, myotube formation, and maturation (39).…”
Section: Discussionmentioning
confidence: 99%